Pengelolaan Pariwisata Halal Pekalongan Studi Peran Pedagang Kuliner dan Kesejahteraan Masyarakat - Ismanto, Kuat (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2020)
This paper aims to explore the potential of Muslim-friendly tourism for the welfare of the people in Pekalongan Regency Beach. This research was carried out within a framework of field research with a qualitative approach. Primary research data obtained through observation, interviews, and documentation. Researchers make observations in the field, as well as conducting interviews with tourism managers and traders at tourist sites. Secondary data was obtained through a review of books, journal articles, data from agencies, and other sources that fit the research theme. The data obtained were analyzed descriptively-qualitatively to draw conclusions. The results of this study indicate that (1) Pekalongan beach tourism has the potential to be developed into Muslim-friendly tourism. Aspects of tourism, such as attractions, access, amenities, and services in good condition. Only, these aspects of tourism need to be improved, both in quantity and quality. (2) There is community involvement in the management of coastal tourism in Pekalongan Regency. The form of community involvement in tourism management has a difference between Depok Indah Beach and Kisik Wonokerto Beach. In Depok Beach, the community participates as traders, where beach tourism is managed by the Department of Tourism. Manifestation of community involvement in Kisik Beach is to become a manager and trader. In Kisik Beach, attractions are managed by the village government through BUMDes, so the involvement of the local village community is very high. (3) There are a number of benefits to the community through the existence of a tourism object as well as its involvement in becoming a tourism manager and trader in a tourist attraction.